2016
DOI: 10.1158/1535-7163.mct-16-0320
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Roles of Long Noncoding RNAs (lncRNA) in Glioblastoma Development

Abstract: Long non-coding RNA (lncRNA) may contribute to the initiation and progression of tumor. In this study, we first systematically compared lncRNA and mRNA expression between GBM and paired normal brain tissues using microarray data. We found 27 lncRNA and 82 mRNA significantly up-regulated in GBM, as well as 198 lncRNA and 285 mRNA significantly down-regulated in GBM. We identified 138 co-expressed lncRNA-mRNA pairs from these differentially expressed lncRNA and genes. Subsequent pathway analysis of the lncRNA-pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…Similarly, we constructed a lncRNA-gene interaction network by including DElncs and their co-expressed DEGs (p value< 0.05 for Spearman's correlation coefficient). This was built on the assumption that lncRNAs may regulate their target genes, although they may not directly bind to the genes [32].…”
Section: Construction Of Regulatory Network For Hfmentioning
confidence: 99%
“…Similarly, we constructed a lncRNA-gene interaction network by including DElncs and their co-expressed DEGs (p value< 0.05 for Spearman's correlation coefficient). This was built on the assumption that lncRNAs may regulate their target genes, although they may not directly bind to the genes [32].…”
Section: Construction Of Regulatory Network For Hfmentioning
confidence: 99%
“…[9][10][11][12] However, the bio-functions and molecular mechanisms of lncRNAs in Wilms' tumour remained largely unknown.…”
mentioning
confidence: 99%
“…Several studies have shown the association between aberrant lncRNA expression and different types of cancers [27,28]. In recent years, some efforts have been made to uncover dysregulated lncRNAs in GBM through gene microarray or RNA-sequencing [29][30][31]. However, no study has focused on the ceRNA network which reflecting lncRNA-miRNA-mRNA interaction or regulation pairs for GBM.…”
Section: Discussionmentioning
confidence: 99%